ExCo Meeting, Dublin (Ireland) 14 July 2013 - (:unkn) unknown (AESOP, 2013)
This is the material for the Executive Committee Meeting, held in Dublin (Ireland) 14 July 2013 AGENDA PAST (10:05–10:30): 1. Short reflection on theGdansk meetings, and the period towards Dublin (ALL) 2. Confirmation of the minutes from ExCo meeting 11 April 2013, Gdansk (GdR) M1 3. Report from GPEAN meeting in Recife (AF, EB-S) M2 4. Adjustment of the 2013 budget (ThM) 5. Brief report SG (IM) ON-GOING AND FORTHCOMING (10:30–12:30): 1. Financial issues: financial regulations (ThM) M3 2. YA report: Best YA Paper Award, new website, YA-General Assembly (VP) 3. Launch of AESOP Booklet Series C (VP, GdR) 4. ECTP-CEU Recognition of Planning Qualification in Europe (KLN) M4 5. Greening AESOP (KLN) M5 6. Cooperation with ACSP (GdR) 7. Lessons from Dublin (GdR, GS): 7.1. From posters to 5 minute sessions? 7.2. How many free wavers at AESOP conferences? 8. AESOP Congress in Utrecht/Delft: activities, debates and proposals (GS) M6 9. AESOP Congress in Prague: first steps (GS) 10. Brief update of the Joint AESOp-ACSP Congress in Dublin (KLN, GS) 11. CoRep meeting and General Assembly: agenda, and who does what (GdR, IM) 12. Membership applications (IM) 12.1. Ozyegin University, Department of Architecture, Istanbul (Associate membership) 12.2. University of Gothenburg, Department of Conservation (Associate membership) 13. Members to be suspended (ThM) 14. Application for President and Treasurer (GdR, IM) Towards FUTURE (13:30–16:30): Within AESOP 1. Council of Representatives: ‘Making Sense Together’ Questionnaire & topics of debates for forthcoming meetings (GdR, IM) 2. CoRep & Heads of Schools Meeting in winter or spring: results from Questionnaire (GdR) 3. Head of Schools meeting: How to enhance the forthcoming meetings? (GdR) 4. YA vision towards the future (VP) 5. Thematic Groups moving forward (EB-S, IM) AESOP interacting with other parties 6. AESOP cooperation with partner organizations (IM, GdR) 6.1. ACSP / GPEAN 6.2. IFHP: Lecture Series, EUSS, YPPA, 6.3. ISOCARP: Invitations Brisbane, Joint Working Group on planning education, YPPA, 6.4. ECTP-CEU: Recognition of Planning Profession, 6.5. ERSA: Joint Winter School 6.6. Decade of Planning (ECTP-CEU – IFHP – ISOCARP): European Urban Summer School, 6.7. European agenda for partners’ cooperation, BELO 7. AESOP Policy within GPEAN (AF, GdR) 8. AESOP Development (GdR) 8.1. Projects: ‘Sense of History’ initiative 8.2. Publishing Policy (going digital): InPlanning / Booklets Series / Lecture Series / Development of website 8.3. Expert pool: why doesn’t it work? (KLN) M7 9. AOB 10. Conclusions (GdR) The item contains the following files (zipped): aesop-exco-meeting-14-07-2013-dublin-agenda-05-07-2013.pdf exco-meeting-11-04-2013-gdansk-minutes-25-06-2013.pdf m2-gpean-report-2013-03-07-2013.doc m3-aesop-financial-regulations-05-07-2013.pdf m4-kln-summary-on-working-group-on-recogtinion-of-professional-recognition-05-07-2013.pdf m5-kln-proposal-on-aesop-greening-policy-05-07-2013.pdf m6-list-of-tracks-and-co-chairs-aesop-congress-in-utrecht-07-07-2013.pdf m7-kln-proposal-on-expert-pool-improvement-05-07-2013.pdf
Keywords: Dublin; 2013; agenda; minutes; financial regulations; Greeining policy; pool improvement